Parent-child associations in pedometer-determined physical activity and sedentary behaviour on weekdays and weekends in random samples of families in the Czech Republic - Sigmundová, Dagmar; Sigmund, Erik; Vokáčová, Jana; Kopková, Jaroslava (International journal of environmental research and public health, 2014)
This study investigates whether more physically active parents bring up more physically active children and whether parents' level of physical activity helps children achieve step count recommendations on weekdays and weekends. The participants (388 parents aged 35-45 and their 485 children aged 9-12) were randomly recruited from 21 Czech government-funded primary schools. The participants recorded pedometer step counts for seven days (≥10 h a day) during April-May and September-October of 2013. Logistic regression (Enter method) was used to examine the achievement of the international recommendations of 11,000 steps/day for girls and 13,000 steps/day for boys. The children of fathers and mothers who met the weekend recommendation of 10,000 steps were 5.48 (95% confidence interval: 1.65; 18.19; p < 0.01) and 3.60 times, respectively (95% confidence interval: 1.21; 10.74; p < 0.05) more likely to achieve the international weekend recommendation than the children of less active parents. The children of mothers who reached the weekday pedometer-based step count recommendation were 4.94 times (95% confidence interval: 1.45; 16.82; p < 0.05) more likely to fulfil the step count recommendation on weekdays than the children of less active mothers.
Keywords: Fathers; otcové; vztahy mezi rodiči a dětmi; Prevalence; pohybová aktivita; sedavý životní styl; Sedentary Behavior; Česká republika; mužské pohlaví; prevalence; Adult; Overweight; Czech Republic; Walking; dítě; Child; logistické modely; ženské pohlaví; chůze; Humans; Mothers; matky; nadváha; Logistic Models; Parent-Child Relations; dospělí; Motor Activity; Female; lidé; Male